Knowledge-Driven Entrepreneurship The Key to Social and Economic Transformation - Andersson, Thomas; Curley, Martin G.; Formica, Piero; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
The current economic era, characterized by the rapid and global dissemination of information and capital, has been called the "knowledge age," the "entrepreneurial society," and the "intangibles economy," among other labels. Technological and productivity improvements continue to shift the emphasis from the mastery of physical assets (e.g., natural resources, factories) and physical tools (e.g., machines) to that of intangible assets (e.g., education, R&D projects, brands, patents) and socio-cultural tools (e.g., communities of knowledge practice) as the key to a community$1 (Bs economic prosperity. The purpose of this book is to build a bridge between knowledge and entrepreneurship, which have traditionally been separated by the walls of academic disciplines. Building on the pioneering work of Peter Drucker and William Baumol, the authors explore the intricate relationships among knowledge generation, innovation, new business creation, and the institutions that support them. Demonstrating direct links between the flow and application of knowledge, innovations in products and processes, the development of new enterprises, and generation of economic wealth, the authors strongly argue that these assets must be protected and sustained through national and regional institutions that encourage creativity and experimentation. Employing illustrative examples from around the world, the authors focus on the crucial role of societies to educate and support entrepreneurs and establish the right environment for new business development and rapid conversion of ideas into enterprises that contribute to economic growth and prosperity.s
Knowledge -- Scenario Setting -- Foundation Laws of Knowledge Dynamics -- The Knowledge Value Chain -- Industry and Knowledge Clusters -- Embracing Business Ecosystems to Enable Sustainable and Accelerated Innovation -- Corporate Management of Knowledge -- Knowledge-Relevant Economic Policy: Analyzing Knowledge Policymaking in Managed and Free-Market Economies -- Global Advance of the Knowledge Economy -- Entrepreneurship -- The Entrepreneurial Revolution -- Types of Entrepreneurs -- Entrepreneurial and Corporate Universities -- Small Business and Entrepreneurial Growth Companies -- Native and International Entrepreneurship -- Laboratory Experiments as a Tool in Empirical Economic Analysis of High-Expectation Entrepreneurship.
Keywords: Economics; Economic policy; Entrepreneurship; Economics/Management Science; Economic Policy; Innovation/Technology Management; Entrepreneurship